Computer game application for JAVA programming language learning / Nurul Hafizah Zainal Abidin ...[et al.] - Zainal Abidin, Nurul Hafizah; Arsad, Roslah; Muslim, Norliana; Masrom, Suraya (UiTM Press, 2020)
Programming is one of the most advanced and valuable skills increasingly adopted by students these days. Learning a programming language is important as it helps to improve the ability to automate, collect, handle, correctly interpret data and information. However, some students have difficulties to internalize the concepts and master the programming skills. Consequently, students tend to perceive programming course as a difficult subject. The objective of this paper is to present the design and implementation of a computer game application that focused on JAVA programming and Bloom’s taxonomy to enhance the students’ understanding. To evaluate the JAVA game application, functional and usability testing have been conducted that involved students from the Diploma of Computer Sciences Program in Universiti Teknologi MARA, Perak, Malaysia. The results were very encouraging as majority of students were satisfied with the JAVA game application by means of programming skill improvement and usability acceptance.